Lao People's Democratic Republic : Selected Issues. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper examines the reform of state-owned banks and enterprises in Lao People's Democratic Republic (Lao PDR). It highlights that recurring high levels of nonperforming loans of state-owned commercial banks have been caused by internal factors, including continued weak credit risk management, lack of skilled and experienced credit personnel, and poor credit culture. The paper outlines the recent and prospective improvements in public expenditure management, and briefly discusses the recent developments in expenditure by focusing on sectoral composition. The paper also summarizes the financial information on the hydroelectric power sector.